Sage nature and the logic of namelessness: Reconstructing he Yan's explication of Dao - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2010)
There is little question that the concept of wu 無, variously translated as “nothing,” “nonbeing,” and “negativity,” is central to the early medieval Chinese intellectual enterprise. Famously, the Jin shu 晉書 (History of the Jin dynasty [265–420]) relates that during the Zhengshi 正始 reign period (240–249) of the Wei dynasty (220–265), He Yan 何晏 (d. 249), Wang Bi 王弼 (226–249), and others established the view, on the basis of their interpretation of the Laozi 老子 and the Zhuangzi 莊子, that all beings “have their roots in wu” (以無為本).